Method and device for growing nano-columns on surface of quartz piece

By growing silica nanopillars on the surface of quartz parts, the problem of poor adhesion of gold coatings was solved, improving adhesion and coating life, while maintaining the transmittance of quartz parts and the reflectivity of gold coatings.

CN121377559APending Publication Date: 2026-01-23ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511525687.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

In existing technologies, gold coatings have poor adhesion to the surface of quartz components and are prone to peeling, which affects equipment performance and coating life. Furthermore, common methods such as sandblasting and chemical etching can damage the quartz surface or cause significant environmental hazards, and the equipment costs are high.

Method used

By growing silica nanopillars on the surface of quartz parts, a mixed solution of polymer stabilizer, alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol is used to react emulsion droplets with silica precursors, thereby controlling the growth density and morphology of nanopillars, improving adhesion, and using a growth device to control the reaction conditions.

Benefits of technology

It improves the adhesion of the quartz component surface, ensures that the thermal expansion coefficient of the nanopillars matches the quartz component material, maintains transmittance, enhances the mechanical interlocking of the gold coating, and extends the coating life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121377559A_ABST
    Figure CN121377559A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor surface engineering, in particular to a method and a device for growing nanorods on the surface of a quartz piece. The method for growing the nanorods on the surface of the quartz piece comprises the following steps: putting the cleaned quartz piece into a mixed solution formed by a polymer stabilizer, an alcohol solvent, a salt stabilizer aqueous solution, a catalyst and ethanol for 10-60 minutes, so that emulsion droplets are adsorbed on the surface of the quartz piece; dropwise adding a silicon dioxide precursor into the mixed solution, and reacting the emulsion droplets with the silicon dioxide precursor to obtain the quartz piece with the nano-columns on the surface. The appearance and density of the nano-columns on the surface of the quartz piece can be regulated and controlled, and the adhesive force of the surface of the quartz piece is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor surface engineering technology, and in particular to a method and apparatus for growing nanopillars on the surface of quartz components. Background Technology

[0002] High-purity quartz components play a crucial role in semiconductor processes, typically operating in extreme environments such as high temperatures and corrosion. Applying specialized functional coatings to the surface of these quartz components is key to improving their performance and extending their lifespan. For example, the gold-plated quartz cavity used in silicon wafer epitaxy equipment effectively reflects radiant heat, reducing heat loss and thus lowering energy consumption. This ensures uniform and stable temperature within the cavity, improving the quality of the epitaxial layer. However, due to the significant difference in thermal expansion coefficients between gold and quartz, and the lack of effective chemical bonding, the gold coating exhibits poor adhesion to the quartz surface, making it prone to peeling and affecting equipment performance and coating lifespan. Summary of the Invention

[0003] This application provides a method and apparatus for growing nanopillars on the surface of quartz parts, which can control the morphology and density of nanopillars on the surface of quartz parts and improve the adhesion of the quartz parts surface.

[0004] To achieve the above objectives, the main technical solutions adopted in this application include:

[0005] In a first aspect, embodiments of this application provide a method for growing nanopillars on the surface of a quartz component, comprising the following steps:

[0006] The cleaned quartz piece is placed in a mixed solution of polymer stabilizer, alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol for 10 min to 60 min, so that the surface of the quartz piece adsorbs emulsion droplets.

[0007] A silica precursor is added dropwise to the mixed solution, and the emulsion droplets react with the silica precursor to obtain a quartz part with nanopillars on its surface.

[0008] The nanopillar growth method on the surface of quartz parts proposed in this application controls the growth density of nanopillars on the quartz part by adjusting the time the quartz part is immersed in the mixed solution and thus controlling the density of emulsion droplets formed on the quartz part surface. This, in turn, improves the adhesion of the quartz part. Furthermore, since the nanopillars formed on the quartz part surface are made of silica, and the silica nanopillars are made of the same material as the quartz part with the same coefficient of thermal expansion, the growth quality of the nanopillars and their adhesion to the quartz part surface are ensured.

[0009] Optionally, the cleaned quartz piece is placed in the mixed solution and sonicated for 10 to 60 minutes.

[0010] In the above embodiments, the ultrasonic action causes the mixed solution to form fine and uniform emulsion droplets, thereby improving the uniformity of the size and morphology of the silica nanopillars formed on the surface of the quartz piece.

[0011] Optionally, the emulsion droplets and the silica precursor are allowed to react statically at 20°C to 60°C to obtain the quartz part with nanopillars on the surface.

[0012] In the above embodiments, the shape of the nanopillars can be controlled by regulating the reaction between the emulsion droplets and the silica precursor.

[0013] Optionally, the emulsion droplets react with the silica precursor first at a first temperature and then at a second temperature, wherein the first temperature is greater than the second temperature.

[0014] In the above embodiments, by setting the first temperature higher than the second temperature, the nanopillar is constructed into an hourglass or cone shape, thereby further improving the adhesion of the quartz component surface.

[0015] Optionally, the polymer stabilizer is polyvinylpyrrolidone, the alcohol solvent is selected from at least one of butanol, pentanol, and hexanol, the aqueous salt stabilizer is an aqueous sodium citrate solution, and the catalyst is ammonia or hydrochloric acid.

[0016] Optionally, the silica precursor is selected from at least one of tetraethoxysilane, methyltrimethoxysilane, hexadecyltrimethoxysilane, aminopropyltrimethoxysilane, and thiopropyltrimethoxysilane.

[0017] Optionally, before placing the cleaned quartz piece in a mixed solution of polymer stabilizer alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol, the quartz piece is ultrasonically cleaned sequentially with acetone, ethanol and deionized water for 10 min to 20 min.

[0018] In the above embodiments, acetone has a strong organic dissolving ability and can remove organic oils and contaminants. Ethanol can further remove residual acetone and perform secondary cleaning. Deionized water thoroughly removes all soluble inorganic salt ions and residual ethanol, and the high purity of deionized water ensures that no new impurities are introduced. Finally, the cleaned quartz part is dried to obtain a quartz part with a clean and controllable surface.

[0019] Secondly, this application provides a growth apparatus for use in the quartz surface nanopillar growth method described in any of the above embodiments. The growth apparatus includes a housing that encloses a reaction chamber. The housing has an opening that communicates with the reaction chamber, and the opening is used to allow a portion of the quartz component to extend into the reaction chamber.

[0020] In the growth apparatus provided in this application, the reaction chamber of the shell is used to contain the mixed solution. The quartz piece can be inserted into the reaction chamber through an opening on the shell, and the position of the quartz piece immersed in the mixed solution can be adjusted according to the location on the quartz piece where the nanopillars need to be grown. The growth apparatus of this application is applicable to both conventionally shaped and irregularly shaped quartz pieces, and the position of the quartz piece immersed in the mixed solution can be adjusted as needed.

[0021] Optionally, the housing includes a bottom wall and a first side wall, the reaction chamber includes a first reaction chamber, the first side wall surrounds the bottom wall and defines the first reaction chamber, and the first side wall is provided with the opening.

[0022] Optionally, the housing further includes a top wall and a second side wall, the reaction chamber includes a second reaction chamber, the second side wall surrounds the top wall and defines the second reaction chamber, and one end of the second side wall away from the top wall is connected to one end of the first side wall away from the bottom wall.

[0023] Optionally, the housing is provided with an ultrasonic rod and / or a stirring rod that extend into the reaction chamber. Attached Figure Description

[0024] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0025] Figure 1 This is a step diagram of a method for growing nanopillars on the surface of a quartz component in one embodiment of this application;

[0026] Figure 2 Scanning electron microscope (SEM) image of a quartz component with a gold coating damaged by nanopillars;

[0027] Figure 3 A comparison chart showing the reflectance of the surface of a quartz part with a gold coating damaged by nanopillars and the surface of a quartz part with a gold coating not damaged by nanopillars.

[0028] Figure 4 This is a scanning electron microscope (SEM) image of a quartz part with nanopillars on its surface coated with a gold coating, according to one embodiment of this application.

[0029] Figure 5 This is a scanning electron microscope (SEM) image of a quartz piece with nanopillars on its surface in one embodiment of this application.

[0030] Figure 6 A comparison of the transmittance of the original quartz surface and the quartz surface with nanopillars.

[0031] Figure 7 A comparison of the reflectance of a raw quartz sample coated with a gold coating and a quartz sample with nanopillars coated with a gold coating.

[0032] Figure 8 This is a schematic diagram of the growth apparatus in one embodiment of this application.

[0033] [Explanation of Labels in the Attached Image]

[0034] 1. Shell; 11. Bottom wall; 12. First side wall; 13. Top wall; 14. Second side wall;

[0035] 2. Reaction chamber;

[0036] 3. Opening;

[0037] 4. Ultrasonic rod; 5. Stirring rod; 6. Quartz component. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0039] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in the description of this application is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms "comprising" and "having," and any variations thereof, in the description, claims, and accompanying drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the description, claims, or accompanying drawings of this application are used to distinguish different objects, not to describe a specific order or hierarchy.

[0040] In this application, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.

[0041] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "attachment" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0042] In this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, in this application, the character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0043] In this application, "multiple" refers to two or more (including two), and similarly, "multiple groups" refers to two or more (including two), and "multiple pieces" refers to two or more (including two).

[0044] To improve the adhesion of quartz parts, methods such as increasing the surface roughness of the quartz (e.g., sandblasting, chemical etching) or adding an intermediate adhesion layer (e.g., Cr, Ti) are commonly used to enhance coating adhesion. However, sandblasting has poor control over the surface structure of quartz parts and can cause surface damage. Chemical etching involves strong acid and alkali reagents that are highly harmful to the environment. The interdiffusion of elements generated by the adhesion layer at high temperatures can weaken the reflective properties of the gold coating on the surface of the quartz parts.

[0045] Fabricating nanostructures on the quartz surface is an effective solution without compromising the quartz's light transmittance, stability, reflectivity, and adhesion of the gold-coated layer. Currently, most commonly used processing methods are top-down techniques, such as using reactive ion etching to etch a quartz substrate with a self-assembled array of polystyrene microspheres to obtain a rough quartz surface. However, these methods are expensive and not suitable for large-volume or irregularly shaped components.

[0046] In addition, silicon carbide is a promising material due to its excellent chemical stability, thermal conductivity and optical properties, but the difference in the coefficient of thermal expansion between quartz and silicon carbide leads to poor growth quality.

[0047] In view of this, this application proposes a method for growing nanopillars on the surface of quartz parts that can improve the adhesion of quartz parts. This method can change the interfacial properties of the quartz parts surface, alleviate the difference in thermal expansion coefficients, and increase the mechanical interlocking between the coating and the quartz parts, thereby improving the adhesion of the coating.

[0048] In a first aspect, embodiments of this application provide a method for growing nanopillars on the surface of a quartz component, comprising the following steps:

[0049] The cleaned quartz part is placed in a mixed solution of polymer stabilizer, alcohol solvent, aqueous salt stabilizer, catalyst and ethanol for 10 min to 60 min, so that the surface of the quartz part is adsorbed with emulsion droplets; a silica precursor is added dropwise to the mixed solution, and the emulsion droplets react with the silica precursor to obtain a quartz part with nanopillars on the surface.

[0050] A polymer stabilizer, alcohol solvent, aqueous salt stabilizer solution, catalyst, and ethanol are prepared into a mixed solution, with ethanol acting as a co-solvent. The polymer stabilizer, alcohol solvent, aqueous salt stabilizer solution, catalyst, and ethanol are mixed uniformly by stirring, sonication, or a combination of both. After stirring, sonication, or a combination of both, the mixed solution forms water-in-oil emulsion droplets. A quartz object is placed in the mixed solution, and the emulsion droplets formed in the mixed solution are adsorbed onto the surface of the quartz object by stirring, sonication, or a combination of both, or by first stirring, sonication, or a combination of both followed by settling. The time for the quartz object to adsorb the emulsion droplets in the mixed solution can be 10 min, 20 min, 30 min, 40 min, 50 min, or 60 min, etc.

[0051] Next, a silica precursor is added dropwise to the mixed solution. Stirring, sonication, or a combination of both can be used to ensure uniform mixing of the silica precursor in the mixed solution, thereby improving the uniformity of contact between the silica precursor and the emulsion droplets. Under the action of the emulsion droplets on the surface of the quartz piece, the silica precursor undergoes hydrolysis and condensation to generate silica, which then grows on the surface of the quartz piece to form silica nanopillars. Specifically, in this application, the reaction between the emulsion droplets and the silica precursor refers to the silica precursor molecules diffusing through the oil phase and further diffusing through the PVP interface film. Under the action of a catalyst, the silica precursor undergoes a hydrolysis and condensation reaction, thereby forming silica, which is then deposited on the surface of the quartz piece to form silica nanopillars.

[0052] For example, after the reaction is completed, the quartz part with nanopillars on the surface needs to be repeatedly washed with deionized water and ethanol and dried to obtain a clean quartz part with nanopillars on the surface without impurities.

[0053] The nanopillar growth method on the surface of quartz parts proposed in this application controls the growth density of nanopillars on the quartz part surface by adjusting the time the quartz part is immersed in the mixed solution and thus controlling the density of emulsion droplets formed by the mixed solution on the quartz part surface, thereby improving the adhesion of the quartz part. Simultaneously, since the nanopillars formed on the quartz part surface are made of silica, and the silica nanopillars are made of the same material as the quartz part with the same coefficient of thermal expansion, the growth quality of the nanopillars and their adhesion to the quartz part surface are ensured. Furthermore, the nanopillars on the quartz part surface do not affect the transmittance of the quartz part.

[0054] For example, the mass fraction of the polymer stabilizer in the mixed solution is 3% to 25%, the mass fraction of the alcohol solvent is 60% to 95%, the mass fraction of the salt stabilizer is 0.005% to 0.1%, the mass fraction of water is 0.6% to 6%, the mass fraction of the catalyst is 0.3% to 3%, and the mass fraction of ethanol is 1% to 10%.

[0055] In addition to adjusting the adhesion time of the emulsion droplets on the surface of the quartz component to regulate the density of the nanopillars, this application also requires sufficient silica precursor to react with the emulsion droplets. For example, the amount of silica precursor added to the mixed solution can be 0.28% to 6% by mass in the mixed solution.

[0056] Optionally, the cleaned quartz piece is placed in the mixed solution and sonicated for 10 to 60 minutes. The sonication causes the mixed solution to form fine and uniform emulsion droplets, thereby improving the uniformity of the size and morphology of the silica nanopillars formed on the surface of the quartz piece.

[0057] Optionally, the emulsion droplets and the silica precursor are allowed to react statically at 20℃ to 60℃ to obtain a quartz part with nanopillars on its surface. The reaction temperature of the silica precursor in the mixed solution can be 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, or 60℃, etc. The reaction temperature can be controlled by placing the growth device on a reheating stage, using a water bath, or adding heating rods inside the internal growth device.

[0058] The reaction between emulsion droplets and silica precursors can occur under isothermal conditions, under fluctuating stable conditions, or by reacting first at a higher temperature and then at a lower temperature, depending on the specific requirements. The shape of nanopillars can be controlled by modulating the reaction between emulsion droplets and silica precursors.

[0059] For example, the reaction of emulsion droplets with a silica precursor under isothermal conditions can form cylindrical silica nanopillars, such as the formation of cylindrical silica nanopillars by reacting the silica precursor at an isothermal temperature of 50°C. It should be noted that the isothermal conditions here can also have temperature fluctuations within a small range.

[0060] Optionally, the emulsion droplets react with the silica precursor first at a first temperature, and then at a second temperature, where the first temperature is higher than the second temperature. The silica precursor reacts at the first temperature to form silica nanopillars with a first diameter, and at the second temperature to form silica nanopillars with a second diameter. If the first temperature is higher than the second temperature, the diameter of the silica nanopillars with the first diameter is smaller than that with the second diameter. Therefore, the overall shape of the silica nanopillars is an hourglass or cone shape, thereby further improving the adhesion to the quartz surface.

[0061] For example, the silica precursor is first reacted at 60°C for 2 hours or 1 hour, then naturally cooled to room temperature, such as 20°C, and then reacted for another 2 hours to form hourglass-shaped silica nanopillars on the surface of the quartz piece.

[0062] When an organic gold coating is brushed or sprayed onto the surface of a quartz part, the hourglass-shaped silica nanopillars can form a strong mechanical interlocking force with the organic gold coating, thereby improving the adhesion of the gold coating to the surface of the quartz part.

[0063] Optionally, the polymer stabilizer is polyvinylpyrrolidone, the alcohol solvent is selected from at least one of butanol, pentanol, and hexanol, the aqueous solution of the salt stabilizer is an aqueous solution of sodium citrate, and the catalyst is ammonia or hydrochloric acid.

[0064] In the mixed solution, the alcohol solvent acts as the external phase, and polyvinylpyrrolidone acts as an interface stabilizer to encapsulate tiny water cores containing hydrochloric acid or ammonia and sodium citrate, forming "water-in-oil" emulsion droplets. When the quartz piece is immersed in the mixed solution, there is a strong affinity between the quartz piece and the emulsion droplets. Under the action of stirring or ultrasound, these emulsion droplets are driven to the surface of the quartz piece and adsorbed on the surface of the quartz piece, providing a basis for the growth of silica nanopillars.

[0065] It should be noted that the alcohol solvent can also be ethanol or propanol. When the alcohol solvent is ethanol, no additional ethanol needs to be added to the mixed solution as a co-solvent.

[0066] Optionally, the silica precursor is selected from at least one of tetraethoxysilane, methyltrimethoxysilane, hexadecyltrimethoxysilane, aminopropyltrimethoxysilane, and thiopropyltrimethoxysilane. One or more silica precursors may be selected according to specific needs.

[0067] Optionally, before placing the cleaned quartz piece in a mixed solution of polymer stabilizer alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol, the quartz piece is ultrasonically cleaned with acetone, ethanol and deionized water in sequence for 10 min to 20 min.

[0068] Acetone has a strong organic dissolving ability and can remove organic oils and contaminants. Ethanol can further remove residual acetone and perform secondary cleaning. Deionized water thoroughly removes all soluble inorganic salt ions and residual ethanol, and the high purity of deionized water ensures that no new impurities are introduced. Finally, the cleaned quartz piece is dried to obtain a quartz piece with a pure and controllable surface.

[0069] In this application, the steps of growing nanopillars on the surface of the quartz part and coating it with a gold coating are as follows: First, the quartz part is pre-cleaned: the quartz part is ultrasonically cleaned with acetone, ethanol and deionized water in sequence for 10 min to 20 min, and then dried for later use.

[0070] Polyvinylpyrrolidone (PVP) and alcohol solvent are then prepared into a polymer alcohol solution with a concentration range of 0.1 g / mL to 0.3 g / mL and a volume of 10 mL to 30 mL. The salt stabilizer aqueous solution is sodium citrate aqueous solution with a concentration range of 0.04 mol / L to 0.06 mol / L and a volume of 200 μL to 600 μL. The catalyst is ammonia (25% by mass) or hydrochloric acid (0.01 mol / L) with a volume of 100 μL to 300 μL and ethanol with a volume of 0.4 mL to 1 mL. The above solutions are mixed evenly to obtain a mixed solution. The cleaned quartz parts are immersed in the mixed solution and emulsified by sonication for 10 min to 60 min.

[0071] After emulsification, a silica precursor is slowly added dropwise to the mixed solution under ultrasonication. The amount of silica precursor used is 100 μL to 600 μL. The reaction is allowed to proceed for 1 h to 24 h at a specified temperature of 20 °C to 60 °C. After the reaction, the quartz component is removed and repeatedly rinsed with deionized water and ethanol, and then dried. An organo-gold coating is then brushed or sprayed onto the surface of the quartz component, followed by high-temperature annealing to obtain a gold coating. The organo-gold coating contains one or more metal additives such as chromium, rhodium, indium, tin, and bismuth to accelerate elemental diffusion at the quartz-coating interface at high temperatures, thereby improving coating adhesion.

[0072] Due to gold's precious metal properties, gold coatings are typically thin. If the silica nanopillars are too tall, the integrity of the gold coating will be compromised, thus reducing reflectivity. (Refer to...) Figure 2 and Figure 3 ,from Figure 2 As can be seen from (a), (b), and (c), the excessive height of the nanopillars damaged the surface of the gold coating. Figure 3The data shows that the reflectivity of the gold coating is reduced due to damage from the nanopillars. Therefore, it is necessary to control the reaction time of the silica precursor in the mixed solution. For example, when the polymer alcohol solution concentration ranges from 0.1 g / mL to 0.3 g / mL, the reaction time of the silica precursor in the mixed solution needs to be controlled within 1 to 3 hours to reduce the probability of the silica nanopillars becoming too long and thus damaging the gold coating. The gold coating can penetrate into the gaps between the silica nanopillars, improving the adhesion of the gold coating. (Refer to...) Figure 4 It can be seen that the gold coating extends into the spaces between the silica nanopillars.

[0073] In one specific embodiment, 1g of PVP was fully dissolved in 15mL of n-hexanol to prepare a polymer alcohol solution; then 147mg of sodium citrate dihydrate was dissolved in 10mL of water to prepare a salt stabilizer aqueous solution; 15mL of polymer alcohol solution, 0.2mL of salt stabilizer aqueous solution, 0.2mL of ammonia, and 0.5mL of ethanol were thoroughly mixed to form a mixed solution. The cleaned quartz piece was then completely immersed in the mixed solution and emulsified by sonication for 60min. Subsequently, 0.3mL of tetraethoxysilane was added dropwise to the mixture under sonication (completely added within 30s). The above reaction solution was placed in a 60℃ water bath and allowed to stand for 1h, followed by natural cooling to room temperature for 2h. After the reaction, the quartz piece was removed, repeatedly rinsed with deionized water and ethanol, and dried to obtain a quartz piece with hourglass-shaped nanopillars on its surface. (Reference) Figure 5 , Figure 5 a represents the distribution of nanopillars on the surface of the quartz component. Figure 5 Figure b shows the growth of a single nanopillar. The hourglass-shaped nanopillars on the surface of the quartz piece have a relatively small impact on its transmittance. (And refer to...) Figure 6 It can be seen that the transmittance of the original quartz piece without nanopillars on the surface is basically the same as that of the quartz piece with nanopillars on the surface.

[0074] Next, an organic gold coating was brushed onto the surface of the quartz part with hourglass-shaped nanopillars, and then annealed at 850℃ for 20 minutes to obtain a quartz part with a gold coating. Tests showed that the hourglass-shaped nanopillars on the surface of the quartz part had little effect on the reflectivity of the gold coating. Figure 7 It can be seen that the transmittance of the original quartz part without nanopillars after being coated with a gold coating is basically the same as that of the quartz part with nanopillars after being coated with a gold coating. Further nano-scratch testing to assess the adhesion of the nanopillars shows that the adhesion of the nanopillars to the gold coating is increased by 24%.

[0075] Secondly, refer to Figure 8This application provides a growth apparatus for growing nanopillars on the surface of a quartz piece 6 in any of the above embodiments. The growth apparatus includes a housing 1, which encloses a reaction chamber 2. The housing 1 has an opening 3 that communicates with the reaction chamber 2. The opening 3 is used to allow a portion of the quartz piece 6 to extend into the reaction chamber 2.

[0076] The reaction chamber 2 of the housing 1 is used to contain the mixed solution. The quartz piece 6 can be inserted into the reaction chamber 2 through the opening 3 on the housing 1, and the position of the quartz piece 6 immersed in the mixed solution can be adjusted according to the location where the nanopillars need to be grown. The opening 3 can be located on one or multiple sidewalls, depending on the specific situation. The growth apparatus of this application is applicable to both conventionally shaped and irregularly shaped quartz pieces 6, and the position of the quartz piece 6 immersed in the mixed solution can be adjusted as needed.

[0077] Optionally, the housing 1 includes a bottom wall 11 and a first side wall 12, the reaction chamber 2 includes a first reaction chamber 2, the first side wall 12 surrounds the bottom wall 11 and defines the first reaction chamber 2, and the first side wall 12 is provided with an opening 3.

[0078] The opening 3 is provided on the first side wall 12. The number and position of the opening 3 can be determined according to the specific use. As long as the first side wall 12 is provided with an opening 3 for the quartz piece 6 to extend into the first reaction chamber 2, the position of the extension can be adjusted according to the area where the nanopillar needs to be grown.

[0079] Optionally, the housing 1 further includes a top wall 13 and a second side wall 14, the reaction chamber 2 includes a second reaction chamber 2, the second side wall 14 surrounds the top wall 13 and defines the second reaction chamber 2, and one end of the second side wall 14 away from the top wall 13 is connected to one end of the first side wall 12 away from the bottom wall 11.

[0080] The first sidewall 12 and the second sidewall 14 are sealed together and define the second reaction chamber 2, so that even irregularly shaped quartz pieces 6 can be inserted into the first reaction chamber 2, and nanopillars can be grown on the surface of the quartz pieces 6 inserted into the first reaction chamber 2. The top wall 13 can be detachably connected to the second sidewall 14, or it can be fixedly connected.

[0081] In one specific embodiment, the opening 3 is provided on the first sidewall 12, and the second sidewall 14 is sealed to the first sidewall 12. The second sidewall 14 and the first sidewall 12 together define the size of the opening 3; or the second sidewall 14 is also provided with a groove opposite to the opening 3 on the first sidewall 12. The groove extends from the side where the second sidewall 14 is connected to the first sidewall 12 toward the top wall 13. The second sidewall 14 and the first sidewall 12 together define the size of the opening 3, thereby enabling the growth device to be suitable for the growth of nanopillars of irregular structures and large quartz components.

[0082] For example, along the thickness direction of the bottom wall 11, the first side wall 12 has a first end face, and the second side wall 14 has a second end face, with the first end face and the second end face being sealed together; wherein, along the first direction, the first side wall 12 has a first wall and a second wall disposed opposite to each other, both the first wall and the second wall having an opening 3, the opening 3 penetrating through the first end face, and the second end face abutting against the first end face to close the opening 3, the first direction being perpendicular to the thickness direction of the bottom wall 11.

[0083] Optionally, the housing 1 is provided with an ultrasonic rod 4 and / or a stirring rod 5 extending into the reaction chamber 2. The ultrasonic rod 4 is used to emulsify the mixed solution into "water-in-oil" emulsion droplets. One or more ultrasonic rods 4 may be provided on the housing 1, depending on the specific application. The stirring rod 5 is used to increase the speed of uniform mixing of the mixed solution.

[0084] The housing 1 may be provided with one or more micro-feed ports for slowly introducing the silica precursor, such as by using an injection pump or a peristaltic pump to control the silica precursor injection rate. The first sidewall 12 and the bottom wall 11 may be provided with discharge ports to discharge the waste material after the reaction.

[0085] The inner wall of the casing 1 is made of corrosion-resistant and hydrophobic material or has a hydrophobic surface treatment to prevent the growth of surface nanopillars. It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover a non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0086] The various embodiments in this specification are described in a progressive manner. Similar or identical parts between embodiments can be referred to interchangeably. Each embodiment focuses on describing the differences from other embodiments. In particular, the system embodiments are basically similar to the method embodiments, so the description is relatively simple; relevant parts can be referred to the descriptions in the method embodiments.

[0087] The above description is merely an embodiment of this application and is not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

[0088] Although embodiments of this application have been described in conjunction with the accompanying drawings, those skilled in the art can make various modifications and variations without departing from the spirit and scope of this application, and such modifications and variations all fall within the scope defined by the appended claims.

Claims

1. A method for growing nanopillars on the surface of a quartz component, characterized in that, Includes the following steps: The cleaned quartz piece is placed in a mixed solution of polymer stabilizer, alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol for 10 min to 60 min, so that the surface of the quartz piece adsorbs emulsion droplets. A silica precursor is added dropwise to the mixed solution, and the emulsion droplets react with the silica precursor to obtain a quartz part with nanopillars on its surface.

2. The method for growing nanopillars on the surface of a quartz component according to claim 1, characterized in that, Place the cleaned quartz piece in the mixed solution and sonicate for 10 to 60 minutes.

3. The method for growing nanopillars on the surface of a quartz component according to claim 1, characterized in that, The emulsion droplets and the silica precursor are allowed to react statically at 20°C to 60°C to obtain the quartz part with nanopillars on the surface.

4. The method for growing nanopillars on the surface of a quartz component according to claim 3, characterized in that, The emulsion droplets react with the silica precursor first at a first temperature and then at a second temperature, wherein the first temperature is greater than the second temperature.

5. The method for growing nanopillars on the surface of a quartz component according to claim 1, characterized in that, The polymer stabilizer is polyvinylpyrrolidone, the alcohol solvent is selected from at least one of butanol, pentanol, and hexanol, the aqueous salt stabilizer is an aqueous sodium citrate solution, and the catalyst is ammonia or hydrochloric acid.

6. The method for growing nanopillars on the surface of a quartz component according to claim 1, characterized in that, The silica precursor is selected from at least one of tetraethoxysilane, methyltrimethoxysilane, hexadecyltrimethoxysilane, aminopropyltrimethoxysilane, and thiopropyltrimethoxysilane.

7. The method for growing nanopillars on the surface of a quartz component according to claim 1, characterized in that, Before placing the cleaned quartz piece in a mixed solution of polymer stabilizer alcohol solvent, salt stabilizer aqueous solution, catalyst and ethanol, the quartz piece is ultrasonically cleaned with acetone, ethanol and deionized water in sequence for 10 min to 20 min.

8. A growth apparatus, applied to the method for growing nanopillars on the surface of a quartz part according to any one of claims 1 to 7, characterized in that, The growth device includes a housing (1) that surrounds a reaction chamber (2). The housing (1) has an opening (3) that communicates with the reaction chamber (2). The opening (3) is used to allow a portion of a quartz piece (6) to extend into the reaction chamber (2).

9. The growth apparatus according to claim 8, characterized in that, The housing (1) includes a bottom wall (11) and a first side wall (12). The reaction chamber (2) includes a first reaction chamber (2). The first side wall (12) surrounds the bottom wall (11) and defines the first reaction chamber (2). The opening (3) is provided on the first side wall (12).

10. The growth apparatus according to claim 9, characterized in that, The housing (1) further includes a top wall (13) and a second side wall (14). The reaction chamber (2) includes a second reaction chamber (2). The second side wall (14) surrounds the top wall (13) and defines the second reaction chamber (2). One end of the second side wall (14) away from the top wall (13) is connected to one end of the first side wall (12) away from the bottom wall (11).

11. The growth apparatus according to claim 8, characterized in that, The housing (1) is provided with an ultrasonic rod (4) and / or a stirring rod (5) that extend into the reaction chamber (2).